Physical properties of 2D and 3D ZnO materials fabricated by multi-methods and their photoelectric effect on organic solar cells - Bi, Sheng (Elsevier, 2019)
ZnO material is a crucial layer for organic solar cell due to its excellent photoelectric properties. However, the influence of ZnO fabricated by various methods as well as the effect of 2-dimensional (2D) and 3-dimensional (3D) configuration is still under debate. In this study, a comprehensive study of 2D ZnO made by sol-gel, atomic layer deposition (ALD) method, 3D ZnO nanorods grown from sol-gel seed layer and ALD seed layer was carried out. Scanning electron microscopy (SEM) and atomic force microscopy (AFM) were used to characterize the morphology of thefilms. X-ray photoelectron spectroscopy (XPS) were used to probe bonding nature as well as defects present in different forms of ZnO. Band gap and crystal quality were characterized by UV-vis spectra. The inverted structure of organic solar cells was fabricated using these forms of ZnO, and the I-V curves as well as the power conversion efficiency (PCE) were measured to evaluate the photoelectric property of the synthesized ZnO nanostructures. It is found that 2D ZnO made by the sol-gel method yields the best PCE of 2.53%